2017
DOI: 10.26877/aks.v8i2.1686
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Video Pembelajaran Matematika Berbantuan Macromedia Flash 8 Dengan Pendekatan Kontekstual Pada Materi Program Linier Kelas Xi

Abstract: Abstrak A. PENDAHULUANUndang-undang No. 20 Tahun 2003 tentang Sistem Pendidikan Nasional Bab II Pasal 3 dijelaskan bahwa Pendidikan Nasional bertujuan mengembangkan peserta didik yang cakap, kreatif dan mandiri (Paradesa dkk., 2010). Menurut Murtianto (2014), kegiatan pembelajaran berpusat pada peserta didik, mengembangkan kreativitas, daya nalar, kontekstual, menantang, menyenangkan, menyediakan pengalaman belajar dan belajar dengan berbuat (learning by doing). Mengacu pada hal tersebut, suatu proses pembelaj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 1 publication
0
8
0
5
Order By: Relevance
“…Another finding states that combining videos with appropriate models can create interesting learning activities to improve student competence (Kawka et al, 2021;Suryawan et al, 2021). Other findings also state that videos are effective in significantly increasing student achievement (Mayang Ayu Sunami & Aslam, 2021;Muna et al, 2017). It is concluded that video is very necessary for learning activities so that the objectives can be achieved.…”
Section: Discussionmentioning
confidence: 98%
“…Another finding states that combining videos with appropriate models can create interesting learning activities to improve student competence (Kawka et al, 2021;Suryawan et al, 2021). Other findings also state that videos are effective in significantly increasing student achievement (Mayang Ayu Sunami & Aslam, 2021;Muna et al, 2017). It is concluded that video is very necessary for learning activities so that the objectives can be achieved.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the video also explains the material and uses appropriate grammar to make it easy to understand. The language used in the video influences students' later understanding (Muna et al, 2017;Pamungkas et al, 2018;Zhang et al, 2022). It causes the use of language to have a major influence on learning.…”
Section: Discussionmentioning
confidence: 99%
“…Temuan lainnya juga menyatakan bahwa model pembelajaran yang dapat membangkitkan keaktifan siswa tentu akan meningkatkan pemahaman dasar siswa dalam belajar (Bdiwi et al, 2019;Devi & Bayu, 2020). Temuan lainnya juga menyatakan bahwa media inovatif dapat meningkatkan gairah belajar siswa menjadi lebih semangat ketika mengikuti pembelajaran (Gowasa et al, 2019;Muna et al, 2017). dengan demikian maka dapat disimpulkan bahwa model pembelajaran aktif dengan menggunakan media Media fun thinkers berbasis literasi soal ini berpengaruh terhadap hasil belajar siswa terutama pada tema pertumbuhan dan perkembangan makhluk hidup.…”
Section: Pembahasanunclassified